FORMATION OF HEALTHY THINKING IN NEIGHBORHOODS AND YOUNG PEOPLE - Jamshidbek Rasulov (Galaxy International Interdisciplinary Research Journal, 2022)
The neighborhood has been a social, cultural, spiritual and educational unity, a place of solidarity and embodiment in the history of our people.